O modelo padrão no ensino médio: um tratamento elementar - Gomes, Roberto Rodrigues (2017)
Due to the importance of the teaching of Modern and Contemporary Physics (MCP) in basic education, especially in high school, and the technologies developed as of the end of the 19th century, as well as their applications, in this dissertation we contribute with the study of an important area of MCP: The Standard Model. For better understanding of this topic, we have adopted various methods, like ludic game, practical activity, technical visits (physical and virtual), and videos, among others. We want to achieve with these methodologies the understanding of the characteristics of the constituent elementary particles of matter, of the forces of interaction, the need for the construction of particle accelerators and the technologies involved in their construction that, directly or indirectly, contribute to society-oriented technologies in different areas of knowledge, such as: communications, medical, food, security, among others. Initially, we made a historical recurrence on the constitution of matter, beginning with Democritus and Aristotle's thoughts, until we get to the beginning of the 19th century of our era. Sequentially, we approach the atomic models of Dalton, Thomson, Rutherford, Bohr and Sommerfeld. We finish the theoretical part of this dissertation with a chapter on the Standard Model, which is our priority. In it we describe the Standard Model theories, technologies and the impacts MCP has on countries' economies. For the development of this dissertation, we adopted the theoretical reference championed by David Ausubel, which considers that the spontaneous knowledge of the student is the most important content that he brings to the classroom.